Postpartum Seizure and Subarachnoid Haemorrhage Secondary to Moyamoya Disease - L. Chitra Varanasi; James Brown; Neil Athayde (Hindawi Limited, 2019)
Postpartum seizures secondary to subarachnoid haemorrhage (SAH) are rare. The incidence of pregnancy-related SAH is increasing and is highest during the delivery and postpartum periods. While there have been cases in the literature of SAH occurring postpartum, very few are associated with Moyamoya disease. We present a rare case of a young woman diagnosed with Moyamoya disease following immediate postpartum seizures secondary to a SAH. She was medically managed and discharged without any neurological deficits. This case highlights how seizures and SAH may develop in the immediate postpartum period in an otherwise healthy young woman.